2012
DOI: 10.1111/j.1744-7402.2012.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zirconia Concentration on the Growth of Nanowires in Bioactive Glass–Ceramic Coatings

Abstract: Bioactive glass-ceramic with various zirconia concentrations was applied on stainless steel (SS) by the sol-gel method. Bioactive glass powder was prepared by the sol-gel method, and thermal properties of the prepared powders were studied by differential thermal analysis (DTA). The effects of zirconia were investigated to explore the growth of nanowires. The growth model of nanowires, in this study, is proposed in terms of the surface diffusion. The coatings showed the hardness values to be in the range of 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The increased nanoporosity and surface area of the sol-gel-derived BGs allow for their improved cellular response and bioresorbability [14]. Recently, rod-or wire-shaped biomaterial nanoparticles gained attention due to their larger surface area and ability to reinforce nanocomposites when combined with biopolymers [15][16][17]. Despite their advantages, there are only limited studies that have been conducted to prepare BG nanorods or nanowires [18].…”
Section: Introductionmentioning
confidence: 99%
“…The increased nanoporosity and surface area of the sol-gel-derived BGs allow for their improved cellular response and bioresorbability [14]. Recently, rod-or wire-shaped biomaterial nanoparticles gained attention due to their larger surface area and ability to reinforce nanocomposites when combined with biopolymers [15][16][17]. Despite their advantages, there are only limited studies that have been conducted to prepare BG nanorods or nanowires [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to combine great mechanical strength and excellent bioactivity of BGs, they can be successfully used as coatings on inert substrates [82]. Reaction to the physiological fluids and the formation of chemical bonding between bones and bioglass can be occurred when bioglasses are implanted in the body [83][84][85][86][87]. A bioactive surface can be considered as important agent to avoid many simultaneous reactions, which take place between the implant and the targeted tissue at the implant surface [82].…”
Section: Bioactive Glass In Biomedical Applicationsmentioning
confidence: 99%
“…Kasuga et al [1] confirmed the high bending strength of zirconia-toughened glass-ceramic composite with no degraded after in vivo implintation for 12 weeks, the optimum zirconia content to get high-strength and bioactivity was 30 vol.%. Rabiee and Azizian [6] used composite coating layer of bioactive glass-ceramic with various zirconia concentrations; the hardness test demonstrate that increasing zirconia content lead to rising of coating hardness. Zirconia was used to resolve the issue of ceramic brittleness and the resultant potential failed implants [7].…”
Section: Introductionmentioning
confidence: 99%